Predicting intraindividual changes in learning strategies: the effects of previous achievement - Buško, Vesna (Array, 2013)
Socio-cognitive models of self-regulated learning (eg. Pintrich, 2000) emphasize contextualized nature of learning process, and within-person variation in learning processes, along with between-person variability in self-regulation. Previous studies about contextual nature of learning strategies have moslty focused on the effects of different contextual factors on interindividual differences in learning strategies utilization. However, less attention was given to the question about contextual effects on within-person variability in learning strategies. In this paper, the following questions were explored: (a) whether students exhibit intraindividual variability in learning strategies between two measurement occasions, or not, and (b) to what degree the observed intraindividual variability in selected learning strategies between two learning episodes can be accounted for by achievement after the first learning episode. The research questions were analyzed under the methodological framework of the latent state-trait theory (Steyer, Ferring, & Schmitt, 1992). The sample consisted of 297 first year university students attending Introduction to Psychology course. Selected learning strategies (organization, elaboration, and critical reasoning) were measured by means of adapted version of the Inventar zur Erfassung von Lernstrategien im Studium (Wild i Schiefele, 1994). Participants filled in the questionnaire before the exams on two occasions with a 7-week time lag. Students’ scores on the first exam were obtained from the teacher’s record. Results provide the evidence that there are individual differences in students' changes in the frequency of use of learning strategies at the end of semester (compared to the midsemester). Also, students who scored higher at the first exam exhibited less intraindividual variability in learning strategies utilization.